2023
DOI: 10.1037/cdp0000621
|View full text |Cite
|
Sign up to set email alerts
|

O te peinas, o te haces rolos: Intersectional discrimination, identity conflict, and mental health among Latinx sexual minoritized adults.

Benjamin F. Shepherd,
Roberto Rentería,
Cristalís Capielo Rosario
et al.

Abstract: Objectives: People of color with minoritized sexual identities (e.g., lesbian, gay, bisexual, queer) experience identity-based challenges from outside and within their communities. Through the integrative lens of minority stress theory and intersectionality, the present study examined identity conflict, also known as conflicts in allegiances-the perceived incongruence between one's sexual and ethnic identities-as a statistical mediator of the association between intersectional discrimination (heterosexist disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 94 publications
4
4
0
Order By: Relevance
“…Shepherd et al (2023) found that intersectional distal stressors were associated with mental health through CiA. While this study has confirmed these associations in a sample of Latinx SGD people, Shepherd et al’s (2023) study examined heterosexism and racism separately rather than collectively. Further, additional research is needed to confirm how CiA may serve as an intersectional proximal stressor that indirectly confirms the associations between intersectional distal stress (e.g., intersectional microaggressions) and mental health among broader samples of SGD-BIPOC.…”
Section: Minority Stress Theorysupporting
confidence: 49%
See 4 more Smart Citations
“…Shepherd et al (2023) found that intersectional distal stressors were associated with mental health through CiA. While this study has confirmed these associations in a sample of Latinx SGD people, Shepherd et al’s (2023) study examined heterosexism and racism separately rather than collectively. Further, additional research is needed to confirm how CiA may serve as an intersectional proximal stressor that indirectly confirms the associations between intersectional distal stress (e.g., intersectional microaggressions) and mental health among broader samples of SGD-BIPOC.…”
Section: Minority Stress Theorysupporting
confidence: 49%
“…Further, CiA may serve as a mechanism between intersectional distal stressors and mental health, with Jackson et al (2020) documenting how daily negative intersectional experiences were indirectly associated with negative affect through CiA. Shepherd et al (2023) found that intersectional distal stressors were associated with mental health through CiA. While this study has confirmed these associations in a sample of Latinx SGD people, Shepherd et al’s (2023) study examined heterosexism and racism separately rather than collectively.…”
Section: Minority Stress Theorymentioning
confidence: 62%
See 3 more Smart Citations